2012
DOI: 10.1002/nbm.2772
|View full text |Cite
|
Sign up to set email alerts
|

Increased ventricular lactate in chronic fatigue syndrome. III. Relationships to cortical glutathione and clinical symptoms implicate oxidative stress in disorder pathophysiology

Abstract: Chronic fatigue syndrome (CFS) is a complex illness, which is often misdiagnosed as a psychiatric illness. In two previous reports, using 1H MRSI, we found significantly higher levels of ventricular cerebrospinal fluid (CSF) lactate in patients with CFS relative to those with generalized anxiety disorder and healthy volunteers (HV), but not relative to those with major depressive disorder (MDD). In this third independent cross-sectional neuroimaging study, we investigated a pathophysiological model which postu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
181
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(197 citation statements)
references
References 50 publications
13
181
2
1
Order By: Relevance
“…Oxidative imbalance has been detected in striated muscle and was correlated with empirical markers of muscle fatigability in the patients examined [289]. Finally, a relatively recent study utilizing NMR spectroscopy reported significantly impaired production of cortical glutathione in people diagnosed with CFS [283].…”
Section: Nitrosylation In Cfs and Depression Chronic Fatigue Syndromementioning
confidence: 93%
See 2 more Smart Citations
“…Oxidative imbalance has been detected in striated muscle and was correlated with empirical markers of muscle fatigability in the patients examined [289]. Finally, a relatively recent study utilizing NMR spectroscopy reported significantly impaired production of cortical glutathione in people diagnosed with CFS [283].…”
Section: Nitrosylation In Cfs and Depression Chronic Fatigue Syndromementioning
confidence: 93%
“…Chronically elevated oxidative stress is almost universally reported by authors investigating this phenomenon in CFS patients, with established highly significant associations between O&NS biomarkers and CFS symptom [208,[279][280][281][282][283][284][285][286]. In an elegant study, Miwa and Fujita showed that a sharp decrease in oxidative stress was associated with clinical remission [287].…”
Section: Nitrosylation In Cfs and Depression Chronic Fatigue Syndromementioning
confidence: 97%
See 1 more Smart Citation
“…Recent developments in MRS spectra have enabled in vivo quantification of GSH from specific brain regions [81]. Only a small handful of studies have assessed in vivo brain GSH levels by MRS in patients with CNS conditions-epilepsy [83,84], schizophrenia [85][86][87], multiple sclerosis [88,89], bipolar disorder [90,91], and mood depressive disorder [91,92]. Recent work has added to this body of work by assessing GSH levels in brains of MCI and AD patients [68,69].…”
Section: Potential Of Gsh Quantitation With Mrs As a Biomarkermentioning
confidence: 97%
“…[1][2][3] Infection has been reported with a wide range of viruses and bacteria, 4 including Epstein-Barr virus, [5][6][7][8] human herpes viruses 6 and 7, [9][10][11] enteroviruses, 7,12 cytomegalovirus 13,14 and lentiviruses, 15 as well as chlamydia, 7 mycoplasma 16 and borrelia species. 17 An association of ME/CFS with central nervous system (CNS) dysfunction is supported by imaging studies documenting cerebral hypoperfusion and increased white matter T2 signal consistent with chronic inflammation 18 in addition to regional differences in gray 19 and/ or white matter. 19,20 Routine cerebrospinal fluid (CSF) studies in patients with ME/ CFS, including white blood cell count, glucose and protein, are typically unremarkable; 21 however, high resolution mass spectrometry has shown abnormalities in the CSF proteome, including an increase in proteins related to the complement cascade.…”
Section: Introductionmentioning
confidence: 98%